Analysis of intestinal parasitic infections seen in the Southeastern Anatolia Region tertiary hospital between 2019-2024 (Annals of Medical Research, 2025)
Aim: The objective of this study was to determine the prevalence of intestinal parasites over time among patients who presented with dyspeptic complaints and sought stool samples from a Turkish tertiary hospital, and to investigate the correlation between intestinal parasites and age and gender.Material and Methods: A retrospective study was conducted between 2019 and 2024 at Siirt Education and Research Hospital to determine the intestinal parasites (IP) trend. We assessed the association between IP and age and gender groupings, as well as the distribution of IP types by year. Stool samples were analyzed using the nativ-lugol technique under a direct light microscope. All data lacking sociodemographic characteristics and the year of stool examination were excluded from the study.Results: Data from 6291 patients were analyzed. In total, 56.9% of the patients were male. The presence of parasites  in accord with the gender did not differ significantly (p=0.528). The prevalence of parasites was 5.7% in the 18–65 age group and 9.0% in the over-65 age group(p=0.006). The most common IP species were E. histolytica (48.3%), B. hominis (28.2%), and G. intestinalis (22.5%, n=84). The incidence of H. nana (1.1%, n=4) was very low.Conclusion: IP is a serious threat to health, particularly in developing countries. The prevalence of IP will decrease as our awareness increases together with efficient diagnosis, treatment, and prevention strategies.
Keywords: Intestinal parasites; Trend analysis; Turkey